Шляхи вдосконалення автомобільних пунктів пропуску митного кордону України у контексті економічної безпеки - Попроцька, О.С. (Культура народов Причерноморья, 2013)
Стаття присвячена актуальній тематиці визначення перспектив облаштування митного
кордону України. В рамках публікації запропоновано Концепцію розвитку автомобільних пунктів
пропуску, сформульовано її головну мету, орієнтири, принципи, основні механізми реалізації та етапи.
Наведено критерії якості та кількості облаштування митного кордону України. Запропоновані напрями
розбудови митного кордону України у розрізі об’єктів будівництва, з урахуванням пропускної здатності
міжнародних автомобільних доріг, у контексті забезпечення економічної безпеки.
Ключові слова: міжнародні транспортні коридори, економічна безпека держави, транспортно-митна
інфраструктура, автомобільний пункт пропуску. Статья посвящена актуальной тематике, в которой определены перспективы
обустройства таможенной границы Украины. В рамках публикации предложено Концепцию развития
автомобильных пунктов пропуска, сформулированы ее главная цель, ориентиры, принципы, основные
механизмы реализации и этапы. Обозначены критерии качества и количества обустройства
таможенной границы Украины. Предложены направления развития таможенной границы Украины с
учетом пропускной способности международных автомобильных дорог в контексте обеспечения
экономической безопасности.
Ключевые слова: международные транспортные коридоры, экономическая безопасность государства,
транспортно-таможенная инфраструктура, автомобильные пункты пропуска. The article is devoted to actual topics determine the prospects arrangement customs border of
Ukraine. During the publication of the proposed concept car points. Formulated its main goal - the customs
border of the European level, which will ensure the growth of the overall level of economic security. Reference
Concept protect national economic interests, the use of geo-economic position, the improvement process
improvement customs border of Ukraine. The mechanisms of Concept - definition of common requirements for
major construction projects, development of model projects of construction and design algorithm for computing
the capacity of crossing points for the design of building, improvement of existing transport and customs
infrastructure and implementing the use of new development, improvement of the distribution of capital
investments in the development of customs border, monitoring the level of improvement of the customs border in
the context of economic security. The implementation of the concept proposed to implement in three stages. At
each stage of the development of certain areas of the customs border of Ukraine, construction sites and
considered the capacity of international highways.
Key words: international transport corridors, economic safety of the state, customs infrastructure, car entry
point.